2005
DOI: 10.1017/s1366728905002142
|View full text |Cite
|
Sign up to set email alerts
|

Contact-induced linguistic innovations on the continuum of language use: The case of French in Ontario

Abstract: In this paper we present a methodological approach that can be used to determine the likelihood that innovations observed in a minority language are the result of language contact. We then use this methodological approach to frame a discussion of data concerning eight innovations that can be attributed to transfer from the majority language (English) The theoretical concept of INTERFERENCE has attracted more than its share of criticism. In our view, the generally 'bad press' it has received is not due to a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 3 publications
1
58
0
1
Order By: Relevance
“…Baker and Jones (1998) noted that preschool minority language children are very vulnerable to the status of English which surrounds them, and tend to shift to English quickly. Influences on the children's L1 have also been observed, and Mougeon, Nadasdi and Rehner (2005) have examined innovations observed in the French of Canadian Francophones which are the result of language contact. Beniak (1994, 1991) looked at attenuation and shift among these young Francophones in Canada and argued the need for institutional support for the minority language L1 speakers.…”
Section: Chi:1 Ir Nomentioning
confidence: 99%
“…Baker and Jones (1998) noted that preschool minority language children are very vulnerable to the status of English which surrounds them, and tend to shift to English quickly. Influences on the children's L1 have also been observed, and Mougeon, Nadasdi and Rehner (2005) have examined innovations observed in the French of Canadian Francophones which are the result of language contact. Beniak (1994, 1991) looked at attenuation and shift among these young Francophones in Canada and argued the need for institutional support for the minority language L1 speakers.…”
Section: Chi:1 Ir Nomentioning
confidence: 99%
“…Third, for one informant from the bilingual group it could be shown that Dutch was activated during language production, because he produced a hybrid collocation which consisted of the French verb chercher and the Dutch preposition naar. Fourth, it is well known that Dutch learners of French often produce the form chercher après (Desmet et al, 2004), while Anglophone learners of French use the forms chercher pour or regarder pour (Mougeon et al, 2005). The most likely explanation for the differences is that they are the result of transfer or pattern replication (Heine & Kuteva, 2005;Matras & Sakel, 2004) from the students' first language.…”
Section: Discussionmentioning
confidence: 99%
“…In Brussels French and in the VALIBEL corpus, regarder pour and chercher pour are not attested, and no mention is made of regarder après or chercher après in Ontario French. After completing a detailed comparison of the use of these verbs in a variety of data from speakers, Mougeon and colleagues conclude that the source of the innovations in Ontario French is likely to be English, because degree of contact with the source language English explains the frequency of occurrence of these forms (Mougeon et al, 2005). As we have seen in section 6.1, Mougeon et al (2005, p. 108) also note that the use of the verb regarder with the preposition pour, which together encode the meaning 'to seek' (a calque from 'to look for'), represents a more in-depth form of contact-induced change than the use of chercher pour because the former entails not only the insertion of pour, but also the substitution of regarder for chercher, whereas the latter only involves the addition of a preposition.…”
Section: Comparison With Data From Belgian French and Canadian Frenchmentioning
confidence: 99%
See 1 more Smart Citation
“…Bullock and Gerfen (2004 : 95) remark that "most work on the role of convergence in attrition has focused on aspects of the morpho-syntactic restructuring of the attriting language", such as Austin (2006), King (2005), Morimoto (2002), and Rottet (1998) among others. Accordingly, Mougeon et al (2005) lay out a four-step methodology for determining whether contact-induced linguistic changes are due to intersystemic transfer, whether this transfer be overt (syntactic) or covert (morphological or semantic), or intra-systemic transfer (Mougeon et al, 2005 : 102-104). Examples of morphological and syntactic effects of language contact include calques, simplification of gender distinctions, and verb positioning (Bullock and Gerfen, 2004:99) as well as analogical leveling (Dorian, 1977 : 29).…”
Section: Models Of Variation In Otmentioning
confidence: 99%